Characterization of the restriction site of a prokaryotic intron-encoded endonuclease. - Chu, F K (1990)
The 1016-base-pair (bp) intron in the T4 bacteriophage thymidylate synthase gene (td) contains a 735-bp open reading frame that encodes a protein product with endonucleolytic activity. The endonuclease shows specificity for the intronless form of the td gene. Highly purified endonuclease cleaves the DNA of the intronless form of the td gene in vitro at 24 bp upstream of the exon 1-exon 2 junction, generating a 2-base staggered cut with 3'-hydroxyl overhangs. Although the endonuclease cleaves in exon 1, it requires some exon 2 sequence for recognition. The maximum recognition sequence lies in an 87-bp stretch, from 52 bp upstream to 35 bp downstream of the cleavage site, ending at 11 bp into exon 2. The td intron endonuclease appears involved in the conversion of the intronless form of td to intron-containing td gene in the T-even phages. A role for intron mobility is discussed.